Особенности повышения производительности сварки плавящимся электродом в защитных газах за счет активации дуги - Савицкий, А.М.; Савицкий, М.М.; Шкрабалюк, Ю.Н. (Проблемы машиностроения, 2014)
Изложены результаты применения активирующих флюсов при сварке плавящимся электродом в защитных газах. Показано, что активирующие флюсы обеспечивают увеличение в 2-3 раза глубины проплавления и повышение производительности сварки по сравнению с традиционным способом. Кроме этого, применение активирующих флюсов обеспечивает уменьшение погонной энергии сварки, что оказывает положительное влияние на свойства сварных соединений, повышая их хладостойкость. Викладено результати застосування активуючих флюсів при зварюванні плавким електродом в захисних газах. Показано, що активуючі флюси забезпечують збільшення в 2-3 рази глибини проплавлення та підвищення продуктивності зварювання порівняно з традиційним способом. Крім цього, застосування активуючих флюсів забезпечує зменшення погонної енергії зварювання, що позитивно впливає на властивості зварних з’єднань, підвищуючи їх холодостійкість. One of the priorities of arc welding is to improve its performance. The traditional solution to this problem involves increasing the amount of metal per unit of time weld. This is due to the limited capacity of the penetrating arc. However, this increases the attachment of heat in the weld, which adversely affects its quality. To solve this problem requires a fundamentally different approach - an increase in the penetration depth. This can be achieved by increasing the penetrating power of the arc by reducing the diameter of the electrode wire or the use of activating fluxes. Studies indicate that by reducing the diameter of the electrode wire can achieve a substantial increase in the penetration depth. However, the practical implementation of this direction is associated with a number of technical difficulties. The second direction of solving this problem is the development and application of welding consumable electrode activating fluxes by analogy with ATIG-welding.